Current antibiotic resistance patterns of rare uropathogens: survey from Central European Urology Department 2011-2019 - Hrbacek, Jan; Cermak, Pavel; Zachoval, Roman (BMC urology, 2021)
BACKGROUND: While the resistance rates of commonly detected uropathogens are well described, those of less frequent Gram-negative uropathogenic bacteria have seldom been reported. The aim of this study was to examine the resistance rates of less frequent uropathogenic Gram-negatives in a population of patients treated in a Department of Urology of a tertiary referral centre in Central Europe over a period of 9 years. METHODS: Data on all positive urine samples from urological in- and out-patients were extracted form the Department of Clinical Microbiology database from 2011 to 2019. Numbers of susceptible and resistant isolates per year were calculated for these uropathogens: Acinetobacter spp. (n = 74), Citrobacter spp. (n = 60), Enterobacter spp. (n = 250), Morganella morganii (n = 194), Providencia spp. (n = 53), Serratia spp. (n = 82) and Stenotrophomonas maltophilia (n = 27). Antimicrobial agents selected for the survey included: ampicillin, amoxicillin/clavulanic acid, piperacillin/tazobactam; cefuroxime, cefotaxime, ceftazidime and cefepime; ciprofloxacin and ofloxacin; gentamicin and amikacin; ertapenem, meropenem and imipenem; trimethoprim-sulfamethoxazole (co-trimoxazole), nitrofurantoin and colistin. RESULTS: Penicillin derivatives have generally poor effect except piperacillin/tazobactam. Cefuroxime is not efficient unlike cefotaxime (except against Acinetobacter spp. and S. maltophilia). Susceptibility to fluoroquinolones is limited. Amikacin is somewhat more efficient than gentamicine but susceptibilities for both safely exceed 80%. Nitrofurantoin shows virtually no efficiency. Cotrimoxazole acts well against Citrobacter spp., Serratia spp. and it is the treatment of choice for S. maltophilia UTIs. Among carbapenems, ertapenem was less efficient than meropenem and imipenem except for S. maltophilia whose isolates were mostly not suceptible to any carbapenems. CONCLUSIONS: Uropathogenic microorganisms covered in this report are noteworthy for their frequently multi-drug resistant phenotypes. Knowledge of resistance patterns helps clinicians choose the right empirical antibiotic treatment when the taxonomical assignment of the isolate is known but sensitivity results are pending.
Keywords: Morganella; centra terciární péče; Enterobacter; Anti-infective agents; Serratia; Humans; infekce močového ústrojí; Urinary tract infections; lidé středního věku; Drug resistance; Stenotrophomonas; Female; Aged; senioři; lidé; Acinetobacter; časové faktory; ženské pohlaví; Male; Middle Aged; Retrospective Studies; Drug Resistance, Bacterial; Citrobacter; Czech Republic; urologie; nemocniční oddělení; Gram-Negative Bacteria; Tertiary Care Centers; Urinary; bakteriální léková rezistence; retrospektivní studie; Hospital Departments; Urinary Tract Infections; Česká republika; mužské pohlaví; Urology; Bacterial; Time Factors; Providencia; gramnegativní bakterie